Recent results on heavy-ion induced reactions of interest for neutrinoless double beta decay at INFN-LNS. (December 2020) - Cappuzzello, F.; Agodi, C.; Acosta, L.; Altana, C.; Amador-Valenzuela, P.; Auerbach, N.; Barea, J.; Bellone, J.; Bijker, R.; Bonanno, D.; Borello-Lewin, T.; Boztosun, I.; et al.
Abstract: The NUMEN project aims at accessing experimentally driven information on Nuclear Matrix Elements (NME) involved in the half-life of the neutrinoless double beta decay (0νββ). In this view measurements of Heavy Ion (HI) induced Double Charge Exchange (DCE) reaction cross sections are performed with high-accuracy. In particular, the ( 18 O, 18 Ne) and ( 20 Ne, 20 O) reactions are used as tools for β+β+ and β - β - decays, respectively. In the experiments, performed at INFN - Laboratory Nazionali del Sud (LNS) in Catania, the beams are accelerated by the Superconducting Cyclotron (CS) and the reaction ejectiles are detected the MAGNEX magnetic spectrometer. The measured cross sections are challengingly low (a few nb), being the total reaction cross section much larger (a few b), thus a high sensitivity and a large rejection capability are demanded to the experimental set-up. This limits the present exploration to few selected isotopes of interest in the context of typically low-yield experimental runs. A major upgrade of the LNS facility is under way in order to increase the experimental dataset of more than two orders of magnitude, still preserving the high sensitivity of the present set-up. When accomplished this effort will make the INFN-LNS as the state-of-the-art research infrastructure for the systematic study of all the cases of interest for 0νββ. In this view, frontiers technologies are going to be adopted for the accelerator and the detection systems. In parallel, advanced theoretical models are being developed in order to extract the nuclear structure information from the measured cross sections.